Testing the Environmental Kuznets Curve Hypothesis: Evidence from Egypt, Kenya and Turkey - Bese, Emrah; Kalayci, Salih (International Journal of Energy Economics and Policy, 2019)
In this study, the Environmental Kuznets Curve hypothesis is examined for 3 developing countries which are Egypt, Kenya and Turkey for the period between 1971 and 2014. The EKC hypothesis is examined under two nexus which are GDP, and energy consumption, and GDP, , energy consumption and the square of GDP. The EKC hypothesis is not confirmed for Egypt, Kenya and Turkey, and the growth hypothesis is confirmed for Egypt and Kenya. The neutrality hypothesis is confirmed for Turkey. Unidirectional causality running from to energy consumption is found for Turkey and no causal relationship is found between and GDP for Egypt, Kenya and Turkey. Authorities in Turkey, Egypt and Kenya should continue to invest in emission reduction policies since these policies are likely not to have a detrimental effect on economic growth. These countries are likely to achieve further economic growth without causing environmental degradation since no causal relationship is found between and GDP. Limits of our study are that results are obtained for 3 developing countries and the period between 1971 and 2014 are examined for these countries. Keywords: Environmental Kuznets Curve Hypothesis, International Economics, GDP, Energy consumption JEL Classifications: Q50, F10, Q4 DOI: https://doi.org/10.32479/ijeep.8638